Unveiling the intelligence spectrum: Neuroscientific insights into giftedness - Franco , Annibal Gouvêa; Batista, Melissa Marcílio (Seven Editora, 2024)
This academic work encompasses neurosciences, high abilities, and giftedness. It aims to present a review that integrates areas involving the neurosciences of behavior and cognition, and their contribution to the gifted, potentially proving useful for educators in the field of high abilities and giftedness. The study is justified by the fact that despite the aforementioned assistance to gifted students being controversial and their identification difficult, Brazil’s Resolution No. 4 (2009) establishes operational guidelines for Specialized Educational Assistance in basic education, in the special education modality, which encompasses students with high abilities and giftedness. The methodology used was a narrative review. It is emphasized that an educator who ventures into the neurosciences and learns about brain functioning begins to exercise their work more meaningfully and efficiently, considering that it is possible to relate certain neuroscientific evidence with theoretical-pedagogical bases. DOI:https://doi.org/10.56238/sevened2024.018-012